Bullying behavior and its relationship to children’s self-esteem - Azlin Atika Putri; Yesi Novitasari; Siti Fadillah (Aṭfāluna: Journal of Islamic Early Childhood Education, 2021)
This study aims to determine whether bullying behavior influences children's self-esteem aged 5-6 years in Mutiara Cendekia Early Childhood Education (ECE) in Pekanbaru, Indonesia. This research is quantitative using the simple linear regression formula. The sampling technique used is total sampling. The results showed that bullying behavior is significantly related to the children's self-esteem. It also indicated that children aged 5-6 years who play online games have high self-esteem. While the remaining 43.6% is influenced by other factors not examined. These findings should be a concern to parents and teachers to control the use of online games for children.